Vita contemplativa: gozando del sumo bien (2021)
The mystical and contemplative experience has been throughout the history of the human thinking one way of facing the search for the truth and the righteousness. In this paper the reader will find an approximation to the topic from the mystic perspective of a person who has been able to approach to the contemplative experience in a dialogue with one of the greatest saints of the history of christianism: San Agustin. This reflection is outlined in books called: Casiciaco´s dialogues, known like that for being the first books the Saint wrote in the town of Casiciaco, after his conversion to the Christianism. This article intends to demonstrate in an spontaneous form from the living experience of who has tested the sweet of VITA COMTEMPLATIVA that San Agustin‘s work, and particularly this time period in Casiciaco Casiciaco is influenced by the dialogue of the faith with the reason and that the same saint became himself in a prodigious compendium of these two complementary forms of approaching to the knowledge of the world and God, in a continuous and enricher dialogue.